Platelet-Rich Plasma Supports Proliferation and Redifferentiation of Chondrocytes during In Vitro Expansion - Jeyakumar, Vivek; Niculescu-Morzsa, Eugenia; Bauer, Christoph; Lacza, Zsombor; Nehrer, Stefan (Frontiers in Bioengineering and Biotechnology, 2017)
Articular cartilage regeneration is insufficient to restore sports injuries or defects that can occur from trauma. Treatment options for cartilage repair include autologous chondrocyte implantation (ACI) by isolation, expansion, and reimplantation of healthy donor chondrocytes. Chondrocyte expansion onto 2D substrates leads to dedifferentiation and loss of the cellular phenotype. We aimed to overcome the state of dedifferentiation by biochemical stimuli with platelet derivatives such as platelet rich plasma (PRP) and hyper acute serum (HAS) to achieve sufficient cell numbers in combination with variable oxygen tension. Human articular chondrocytes from osteoarthritic (OA) cartilage chondrocytes were switched from 10% FCS supplementation to either 10% PRP or 10% HAS after initial passaging for further experiments under normoxic (20%O2) or hypoxic (1%O2) conditions. An XTT assay measured the effect of PRP or HAS on the cell proliferation at 3, 6 and 9 days. The chondrogenic redifferentiation potential of dedifferentiated chondrocytes was determined with RT-qPCR for markers of expression for type II collagen (COL2A1), type I collagen (COL1A1) and matrix metalloproteinases MMP3, MMP13 at 24hrs and 72hrs. Measured protein levels of 100% PRP or HAS by multiplex quantification revealed bFGF, G-CSF, PDGF was significantly higher in PRP than in HAS (p<0.05) but LEPTIN levels did not differ. The quantified protein levels did not differ when isolated from same donors at a different time. Chondrocyte proliferation indicated that supplementation of 10% HAS enhanced the proliferation rate compared to 10% PRP or 10% FCS at 6 and 9 days significantly (p<0.05). mRNA levels for expression of COL1A1 were significantly downregulated (p<0.05) when cultured with 10% PRP than 10% HAS or 10% FCS under normoxic/hypoxic conditions. COL2A1 was significantly upregulated (p<0.05) in PRP than 10% HAS or 10% FCS. MMP3 expression was downregulated after 72hrs under all conditions. MMP13 was upregulated with 10% PRP at both 24 and 72 hrs but significantly downregulated under hypoxia (1%O2) for all circumstances. While HAS has its effect on chondrocyte proliferation, PRP enhances both proliferation and redifferentiation of dedifferentiated chondrocytes. PRP can replace standard usage of FCS for chondrogenic priming and expansion as implications for clinical use such as ACI procedures.